Privacy Preserving Features Selection for Data Mining using Machine Learning Algorithms - Anuar N.K.; Bakar A.A.; Ahmad A.R.; Yussof S.; Rahim F.A.; Ramli R.; Ismail R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Data Analytics; Data mining; Decision making; Feature extraction; Machine learning; Predictive analytics; Privacy by design; Features selection; Fine grains; No leakages; Predictive modeling; Privacy preserving; Learning algorithms